2011
DOI: 10.1021/ol200799u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Directly Connected BODIPY Oligomers through Suzuki–Miyaura Coupling

Abstract: Treatment of a meso-arylboron dipyrrin (BODIPY) with NBS provides mono- and dibrominated BODIPYs at the 2- and 6-positions in excellent yields with high regioselectivity. Brominated products can be employed as a nice building block for the synthesis of a variety of BODIPY derivatives through Suzuki-Miyaura coupling. Because of a lack of substituents at the 1,3,5,7-positions, a directly β-β-linked BODIPY dimer exhibits a completely coplanar conformation of BODIPY units, offering effective π-conjugation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(96 citation statements)
references
References 24 publications
4
90
0
2
Order By: Relevance
“…Yield: 9.0 mg, 23%. 65 4BDP-ZnP. Compound 6 (33.0 mg, 97.3 µmol) and pyrrole (6.3 mg, 97.3 µmol) were dissolved in a mixture of dry CHCl 3 (4.7 mL) and ethanol (3.0 µL), and deaerated by bubbling argon gas for 20 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yield: 9.0 mg, 23%. 65 4BDP-ZnP. Compound 6 (33.0 mg, 97.3 µmol) and pyrrole (6.3 mg, 97.3 µmol) were dissolved in a mixture of dry CHCl 3 (4.7 mL) and ethanol (3.0 µL), and deaerated by bubbling argon gas for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…That can be attributed to the coupling of transition dipole moments along the long molecular axis of the hybrids according to the exciton model of Kasha. [61][62][63][64][65][66] To further understand the significantly decrease in the extinction coefficients of B bands of 50 ZnP and the change of BODIPY absorption, time-dependent density functional theory (TDDFT) at the B3LYP/6-31g* level with Polarizable Continuum Model (CHCl 3 ) was applied to calculate the singlet excited states ( The normalized emission spectra of BDP-ZnP, 2BDP-ZnP, and 4BDP-ZnP were measured to show the fluorescence quenching of the BODIPY units of the hybrids (Fig. 4), and the related data 70 was summarized in Table 1.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…[78][79][80] Recently, Shinokubo et al demonstrated a regioselective bromination of 1,3,5,7-unsubstituted BODIPY using 1.2 and 2.4 equivalents of NBS in CH 2 Cl 2 at room temperature to achieve mono-and di-brominated forms, respectively. 81 Pavlopoulos et al di-brominated products. 82 The latter approach has been used extensively in the bromination of aza-BODIPY analogues.…”
Section: E Structural Modification Of Bodipy-based Photosensitizers mentioning
confidence: 99%
“…11 The substitution at meso positions of the boron dipyrrin core with bulky electron rich heterocycles could produce large Stokes Shifts of 100-120 nm. [13][14][15] Such artificial BODIPY dimers have demonstrated that meso-meso and meso-beta linked BODIPY dimers can be used as singlet oxygen photosensitizer in nonpolar organic media. [13][14][15] Such artificial BODIPY dimers have demonstrated that meso-meso and meso-beta linked BODIPY dimers can be used as singlet oxygen photosensitizer in nonpolar organic media.…”
mentioning
confidence: 99%